“What will they say in England?”: violence, anxiety, and the press in nineteenth century New Zealand and Vancouver Island - Storey, Kenton (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2009)
Contemporary British imperial historiography argues that during the late 1850s/early 1860s antagonistic racial discourses became increasingly popular across the British Empire. According to this interpretation, escalating colonial violence and Darwinian racial discourses marginalized the humanitarian tenet that Indigenous peoples could achieve a measure of British civilization. During this same period the British colonies of New Zealand and Vancouver Island featured anxiety related to the threat of indigenous violence. But while New Zealand and Vancouver Island featured remarkable parallels in their colonial development, differing local conditions and relationships to the British metropole contributed to divergent reactions within local press to the threat of indigenous violence. This paper focuses on representative newspapers from New Zealand’s and Vancouver Island’s capital cities. An analysis of Auckland’s Southern Crossand Victoria’s British Colonist provides an opportunity to highlight the effects of colonists’ anxiety, the local resiliency of humanitarian discourses, and the influence metropolitan connections played in the formation of editorial perspectives.